2010
DOI: 10.1007/s12032-010-9505-4
|View full text |Cite
|
Sign up to set email alerts
|

P53 gene polymorphisms and breast cancer risk in Arab women

Abstract: The association between polymorphisms in the p53 tumor suppressor gene and breast cancer risk has been studied in many human populations with conflicting conclusions. However, similar studies in Arab women are not available, and the status of these polymorphisms in this ethnic population is not known. We investigated the status of four known p53 gene polymorphisms and their possible role in breast cancer risk in Arab women. Genotyping was performed for 288 breast cancer women and 188 controls to determine Pro4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 27 publications
10
43
0
Order By: Relevance
“…In the present study, it was found that 100% of the Saudi women involved in the study carried the wild-type sequence CCG (proline) at codon 47 of the TP53 gene. Similar results were reported in the Kuwaiti population, wherein the the codon 47 variant was detected in only one patient and none of the controls (18). Therefore, the rare sequence TCG (serine) of SNP47, which is thought to reduce the p53 apoptosis ability 5-fold as compared with the wild-type p53 proline 47 (7), is extremely rare or non-existent in the Saudi Arab population.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the present study, it was found that 100% of the Saudi women involved in the study carried the wild-type sequence CCG (proline) at codon 47 of the TP53 gene. Similar results were reported in the Kuwaiti population, wherein the the codon 47 variant was detected in only one patient and none of the controls (18). Therefore, the rare sequence TCG (serine) of SNP47, which is thought to reduce the p53 apoptosis ability 5-fold as compared with the wild-type p53 proline 47 (7), is extremely rare or non-existent in the Saudi Arab population.…”
Section: Discussionsupporting
confidence: 79%
“…Similar results have also been reported regarding cervical cancer (17). Furthermore, Alawadi et al and a recent meta-analysis showed the PP genotype to be associated with decreased breast cancer risk among the Kuwaiti and Indian populations, respectively (14,18). However, Dumont et al found that the proline variant is associated with an increased risk of breast cancer (19).…”
Section: Discussionsupporting
confidence: 64%
“…Polymorphisms in the p53 tumor suppressor gene are potential molecular markers for inherited predisposition for breast cancer (Alawadi et al, 2010). The frequency, timing, and mutation spectrum of the p53 can provide clues to the etiology and pathogenesis of human cancer (Hussain et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A study in 2011 found that the TP53 proline mutation did have a profound effect on pancreatic cancer risk among males [9]. A study of Arab women found that proline homozygosity at TP53 codon (72) is associated with a decreased risk for the breast cancer [10] [11] [12]. One study suggested that TP53 codon 72 polymorphisms, p53 mutation still the most common genetic change named in human neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular pathological analysis of the structure and expression of constituents of the p53 pathway is likely to have value in diagnosis, in prognostic assessment and ultimately in treatment of breast cancer [13]. Another study found the suppressor protein 53 homozygous (Pro/Pro) genotype was associated with a significantly increased risk for renal cell carcinoma [10] [14] [15] [16]. According to recent researches, P53 mutations are highly correlated in human breast cancer.…”
Section: Introductionmentioning
confidence: 99%